Selected aspects of oral cavity diseases in menopausal women - Petkowicz, Beata; Piotrkowicz, Jakub; Szeszko, Łukasz; Banakiewicz, Katarzyna; Zieliński, Paweł (Menopause Review/Przegląd Menopauzalny, 2013)
Introduction : During the menopausal period, women undergo many hormonal and biological changes, especially in steroid hormones metabolism. Considering the presence of the estrogen receptors, also in oral cavity, disorders in hormones level directly influence its physiological condition. The aim of the study was to evaluate changes in menopausal women oral cavity. This scientific paper underlines practical data for first contact medical practitioners and dentists taking care of patients in menopausal period. Material and methods : The main material for research is menopause, her influence on oral cavity, as well as the effect of the hormonal replacement therapy based on scientific papers. Results: Changes in oral cavity are common issue for women in menopausal period. The main symptoms of pre and postmenopausal periods are Burning Mouth Syndrome (BMS), pathological changes in oral cavity and Candidosis, followed by general symptoms. Histologically, mucosa of an oral cavity and vagina is similar, thus the pathological change has its common origin. Hormonal Replacement Therapy, used in gynecological disorders, can alleviate the symptoms, also in oral cavity. Conclusions : Women in menopausal period are recommended to be taken care of by gynaecologists and dentists.